Double dielectric modification of nickel foam-based microwave absorbers with improved impedance matching and absorption performances. Issue 23 (1st December 2021) - Kang, Bo; Lu, Xiaochi; Chen, Yu; Xie, Peitao; Jia, Qi; Zhu, Liyan; Liu, Jun; Quan, Bin
Abstract: Proper physical property and well-designed microscopic structures are significant in determining the electromagnetic energy conversion. In this work, nickel foam (NiF )-based rod-like absorbers with double dielectric regulation were achieved via continuous hydrothermal reaction and subsequent heating treatment. The NiF -based uniform integration of binary metal oxides not only maintain the inherent excellent dielectric property of NiF, but also introduce extra dipolar polarizations (caused by multiple covered dielectrics) and Maxwell-Wagner-Sillars effect (induced by large dielectric property differences at the interfaces), which all contribute to the excellent microwave absorption performance. In addition, derived from the high/low dielectric synergetic effect, a balance between the introduction and dissipation of the electromagnetic energy can be realized. Based on that, the maximum bandwidth of NiF -based binary absorber reaches 7.28 GHz at 2.4 mm. This work not only provides a facile and versatile strategy to fabricate NiF -based ternary microwave absorbers, but also demonstrates the significant role of dielectric synergetic effect in optimizing microwave absorption performance.